HUBUNGAN ANTARA UKURAN RUMPANG DAN PERTUMBUHAN DIAMETER TANAMAN ULIN (Eusideroxylon zwageri Teijsm & Binn.) DI KHDTK KINTAP KECAMATAN KINTAP KALIMANTAN SELATAN - Susi Wardani; Basir Basir; Sulaiman Bakri (Universitas Lambung Mangkurat, 2020)
Deforestation and degradation of natural forests and plants reached 1.6-2.0 million ha. Forestry Research and Development Agencies throughout Indonesia have begun to develop various silvicultural techniques of ulin so that the extinction of the plant can be prevented. One of the silvicultural systems that began to be developed was a gap system. The purpose of this study was to determine the growth of ulin (Eusideroxylon zwageri Teijsm & Binn.), and the influence of the size of the gaps on the growth of ulin plants in Kintap KHDTK. The results obtained were the average growth of the lowest ironwood plants from the value of diameter (1.27 cm) that was at without gap treatment, while the highest growth was the best diameter (5.01 cm), which was at the gap with diameter of 12 m. The optimal diameter of ironwood growth is in the size of a 12 m. Treatment of overlays of 12 m gives a good growth effect for ironwod plants.